Rebranding MSMEs Product Brands in Strengthening Visual Identity - Achirsyah Bahar (Jurnal Ekspresi : Desain Komunikasi Visual dan Seni, 2023)
The objective of this study is to enhance the identity of Kopide MSMEs through the implementation of a rebranding strategy and visual identity design. By means of documentation studies, interviews, and qualitative descriptive analysis, this study investigates the concepts of media, communication, and visuals in rebranding. The results demonstrate that establishing consumer confidence, increasing sales, and differentiating MSME products on the market are all dependent on an integrated and consistent brand identity. Rebranding of Kopide MSMEs entails the modification of a logo that symbolises the union of coffee and innovative concepts, as well as the incorporation of colour scheme and typeface choices that reinforce the brand persona. It is anticipated that the outcomes will enhance the market standing of Kopide MSMEs and cultivate a favourable perception among consumers, particularly the millennial demographic.